2018
DOI: 10.3390/met8010030
|View full text |Cite
|
Sign up to set email alerts
|

Ion Implantation of Calcium and Zinc in Magnesium for Biodegradable Implant Applications

Abstract: Abstract:In this study, magnesium was implanted with calcium-ion and zinc-ion at fluences of 10 15 , 10 16 , and 10 17 ion·cm −2 , and its in vitro degradation behaviour was evaluated using electrochemical techniques in simulated body fluid (SBF). Rutherford backscattering spectrometry (RBS) revealed that the implanted ions formed layers within the passive magnesium-oxide/hydroxide layers. Electrochemical impedance spectroscopy (EIS) results demonstrated that calcium-ion implantation at a fluence of 10 15 ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…180 A recent study showed that the Ca ion implantation improved the corrosion resistance, whereas the Zn ion implantation with pure Mg reduced the corrosion resistance. 181 Further, the microstructure near the surface region of Mg alloy can be modified using high density laser beam to improve corrosion resistance. 182,183 Dispersion of hard particles such as titanium carbide (TiC) and silicon carbide (SiC) by laser melting can significantly improve the surface properties of AZ91 alloy.…”
Section: Physical Vapor Deposition (Pvd) and Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
See 1 more Smart Citation
“…180 A recent study showed that the Ca ion implantation improved the corrosion resistance, whereas the Zn ion implantation with pure Mg reduced the corrosion resistance. 181 Further, the microstructure near the surface region of Mg alloy can be modified using high density laser beam to improve corrosion resistance. 182,183 Dispersion of hard particles such as titanium carbide (TiC) and silicon carbide (SiC) by laser melting can significantly improve the surface properties of AZ91 alloy.…”
Section: Physical Vapor Deposition (Pvd) and Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…In contrast to this result, another study found that Zn ion implantation on Mg–Ca alloy surface improved corrosion resistance along with higher hardness and elastic modulus 180 . A recent study showed that the Ca ion implantation improved the corrosion resistance, whereas the Zn ion implantation with pure Mg reduced the corrosion resistance 181 . Further, the microstructure near the surface region of Mg alloy can be modified using high density laser beam to improve corrosion resistance 182,183 .…”
Section: Approaches To Improve Different Properties Of Mg Alloysmentioning
confidence: 99%
“…Magnesium (Mg) and its alloys are widely regarded as the next generation of biomedical materials for its complete degradation in vivo, favorable mechanical strength, and elastic modulus close to natural bone. However, its clinical applications are hampered by its fast corrosion rate, which would lead to the accumulation of hydrogen bubbles and the violent changes of local pH value . Surface modification is the most widely used method to improve its cytocompatibility and corrosion resistance, including electroless plating, , plasma electrolytic oxidation (PEO), , electrodeposition, , hydrothermal treatment, polymer coating, ion implantation, and so on. However, the improved corrosion resistance and cytocompatibility of Mg implants are not sufficient enough to meet the requirement of different clinical application, such as bone implants.…”
Section: Introductionmentioning
confidence: 99%
“…The primary advantages like selective surface modification, low temperature, and reproducibility are significant for coating Mg alloys [ 180 , 181 ]. However, amorphization caused during ion implantation causes surface devoid of grain boundaries, resulting in enhanced corrosion [ 182 ]. As ion implantation is a non-thermodynamic process, studies have reported the generation of compressive residual stresses and increased surface roughness of the ion-implanted surface.…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%